The feasibility of implementing food-based dietary guidelines and food graphics in Ethiopia - Bekele, Tesfaye Hailu; Covic, Namukolo M.; Alemayehu, Dawit; Trijsburg, Laura E.; Brouwer, Inge D.; Feskens, Edith J.; Vries, Jeanne de (Springer, 2023)
This study aimed to test the acceptability, cultural appropriateness, consumers' understanding, and practicality of the Ethiopian food-based dietary guideline's messages, tips, and food graphics. A qualitative study design was applied with focus group discussions and key informant interviews. Four different participant groups were included: 40 consumers, 15 high-level nutrition experts, 30 frontline community health extension workers (HEWs), and 15 agriculture extension workers (AEWs) to incorporate different stakeholder perspectives. Data collection was conducted using 7 focus group discussions (FGDs) and 30 key informant interviews (KIIs). Collected data were coded and analyzed using QSR International NVivo V.11 software. Most of the study participants were highly interested in implementing the dietary guidelines once these guidelines are officially released. Based on the participants' views, most of the messages align with the current nutrition education materials implemented in the country except the messages about physical activity and alcohol intake. However, participants suggested defining technical terms such as ultra-processing, whole grain, safe and balanced diet in simpler terms for a better understanding. Practicality, affordability, availability, and access to the market were the major barriers reported for adherence to the guidelines. To be more inclusive of cultural and religious beliefs, findings show that the guideline should address fasting and traditional cooking methods. In conclusion, the dietary guidelines were well received by most stakeholders. They are thought to be feasible once feedback on wording, affordability, availability, and access is considered in the messages, tips, and graphic designs.